Sex Ratio and Gonadal Maturity of Marble Goby (Oxyeleotris marmorata) in Lake Tempe, Indonesia - Irwan, Nurul Mutiara; Omar, Sharifuddin Bin Andi; Yunus, Budiman (Aquatic Life Sciences, 2025)
Understanding the sex ratio and initial gonadal maturity size of fish populations is essential for effective conservation and sustainable fishery management. This study aims to analyze the comparison of sex ratio and initial gonadal maturity size of marble goby (Oxyeleotris marmorata) in Lake Tempe, Wajo Regency, South Sulawesi. The research was conducted over two months, from October to November 2023, with four sampling events, two during the dark moon phase and two during the bright moon phase. A total of 285 individuals were collected, consisting of 118 females and 167 males, using jabba or bubu fishing gear. Sex identification and gonadal maturity determination were conducted at the Fisheries Biology Laboratory, Faculty of Marine and Fisheries Sciences, Universitas Hasanuddin. The results showed that the overall sex ratio was 0.71:1.00 (female:male), with significant male dominance during the dark moon phase and at Station 1 (near agricultural land). Gonadal maturity levels (TKG) ranged from stage I to stage V, with first gonadal maturity sizes varying between moon phases and locations. The smallest first gonadal maturity size was recorded at 175.72 mm for females (Station 1) and 191.65 mm for males (Station 1). These findings provide essential data for supporting sustainable fishery management in Lake Tempe.